2008
DOI: 10.1039/b800487k
|View full text |Cite
|
Sign up to set email alerts
|

An integrated QCM-based narcotics sensing microsystem

Abstract: We present the design, fabrication and successful testing of a 14 x 14 x 4 mm(3) integrated electronic narcotics sensing system which consists of only four parts. The microsystem absorbs airborne narcotics molecules and performs a liquid assay using an integrated quartz crystal microbalance (QCM). A vertically conductive double-sided adhesive foil (VCAF) was used and studied as a novel material for LOC and MEMS applications and provides easy assembly, electrical contacting and liquid containment. The system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…c Front and backside pictures of two devices. The QCM crystal is visible through the polymer backside cover (Source: Frisk et al 2008) quantification of the detection, such as reaction accompanied by gas production. SPR detection method is growing rapidly, mostly because it is a free labelng and real-time response detection method, and the background noise is virtually eliminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…c Front and backside pictures of two devices. The QCM crystal is visible through the polymer backside cover (Source: Frisk et al 2008) quantification of the detection, such as reaction accompanied by gas production. SPR detection method is growing rapidly, mostly because it is a free labelng and real-time response detection method, and the background noise is virtually eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…The detection limit for protein A is 1 mg/mL. Recently, Frisk et al (2008) reported a novel microsystem which absorbed airborne narcotics molecules and performed a liquid assay using an integrated quartz crystal microbalance (QCM). In this study, the microsystem consisted of four parts.…”
Section: Quartz Crystal Microbalancementioning
confidence: 99%
“…Airborn narcotics detected using an integrated quartz crystal microbalance and a liquid assay have been reported by Frisk et al (92). Portability is an important feature for a microfluidic system.…”
Section: Technologymentioning
confidence: 96%
“…In particular, a robust air-liquid interface is required to allow capture of the aerosol droplets and dispersion of the captured sample in a liquid medium, in which direct initiation of specific ligand-receptor biochemical reactions can occur. We have previously presented microsystem-based components for air-liquid interfacing in combination with downstream analysis, for quartz crystal microbalance (QCM) sensing of airborne narcotics [44,45]. Two examples of such surface tension-based air-liquid interfacing include: pillar forests and perforated diaphragms.…”
Section: Introductionmentioning
confidence: 99%